Clonality Testing in Veterinary Medicine: A Review With Diagnostic Guidelines. (July 2016) - Keller, S. M.; Vernau, W.; Moore, P. F.
The accurate distinction of reactive and neoplastic lymphoid proliferations can present challenges. Given the different prognoses and treatment strategies, a correct diagnosis is crucial. Molecular clonality assays assess rearranged lymphocyte antigen receptor gene diversity and can help differentiate reactive from neoplastic lymphoid proliferations. Molecular clonality assays are commonly used to assess atypical, mixed, or mature lymphoid proliferations; small tissue fragments that lack architecture; and fluid samples. In addition, clonality testing can be utilized to track neoplastic clones over time or across anatomic sites. Molecular clonality assays are not stand-alone tests but useful adjuncts that follow clinical, morphologic, and immunophenotypic assessment. Even though clonality testing provides valuable information in a variety of situations, the complexities and pitfalls of this method, as well as its dependency on the experience of the interpreter, are often understated. In addition, a lack of standardized terminology, laboratory practices, and interpretational guidelines hinders the reproducibility of clonality testing across laboratories in veterinary medicine. The objectives of this review are twofold. First, the review is intended to familiarize the diagnostic pathologist or interested clinician with the concepts, potential pitfalls, and limitations of clonality testing. Second, the review strives to provide a basis for future harmonization of clonality testing in veterinary medicine by providing diagnostic guidelines.